The 45-year evolution of the Mathys RM monoblock cups: have the paradigm shifts been worthwhile?. Issue 2 (March 2023) - Foxall-Smith, Michael; Wyatt, Michael C; Frampton, Christopher; Kieser, David; Hooper, Gary
Introduction: The Robert Mathys (RM) monoblock uncemented cup is a design less commonly used in primary total hip replacement. It's purported advantages over modular cemented cups are: (1) its modulus of elasticity approximating bone, thus mimicking load transmission and the biomechanical behaviour of the cup to better match stresses on the acetabulum, leading to bone-preservation; and (2) as a 1-piece cup there is absence of a mobile interface between a liner and shell, preventing backside wear. Since its inception in 1983 there have been 3 major design changes: the RM Classic, the RM Pressfit, and the RM Vitamys with the most modern polyethylene (vitamin E). Methods: In a retrospective cohort study of the New Zealand Joint Registry, all designs of RM acetabular cup were reviewed. Data were included from1998 to 2018. All-cause revision rates, reasons for revision and the Oxford Hip Score (OHS) were assessed. Results: In total 13, 272 acetabular cups were included. The all-cause revision rates did not differ between the designs. Revision rates for aseptic loosening in the RM Vitamys were lower, but the follow-up was shorter and more larger heads were used. There was no difference in the OHS. Conclusion: All implant designs were safe. The use of larger heads led to a decrease in revisions due to dislocation. It has to be waited out whether the RM Vitamys performs superior in the long-term due to the highly cross-linked polyethylene.